Análise de rodovias de baixo volume de tráfego quanto ao dimensionamento, ocorrência de defeitos e impactos climáticos nos acostamentos - Almeida, Antonia Fabiana Marques (2024)
Low-Volume Roads (LVR) are essential in promoting accessibility to basic services in communities further away from large centers and correspond to more than 60% of the road network in the world. They must be able to provide comfortable and safe transportation to users through adequate and durable structures. The technical regulations for the road environment are aimed at higher volume highways, making LVR unattractive in terms of its efficiency and not a priority in maintenance and rehabilitation actions by managers. In this sense, this work aims to analyze the LVR in the state of Ceará regarding their design, mechanisms of occurrence of defects, and impacts of climate effects on shoulders in their structure, as subsidies to support decision making. To this end, the work was structured into three articles. In Article 1, structures with four different subgrades were analyzed, dimensioned with Resilient Modulus (MR) values estimated by the National Dimensioning Method (MeDiNa), which resulted in a catalog of solutions that do not compromise the useful life in terms of Permanent Deformation (PD) in LVR. In Article 2, the categorized defects available in the federal highway survey reports were analyzed and with ordered logistic regression, the explanatory variables that imply a greater severity of potholes and patches were identified. Article 3 evaluated the influence of shoulders on the structural performance of highways, in which increases in humidity in the granular layers of LVR pavements, through lateral infiltration, cause loss of mechanical resistance, resulting from reductions in average MR values and an increase in PD values. Thus, LVR can be built more efficiently and at low cost with the help of sizing catalogs, and to protect these pavements, shoulders must be built, preferably with the same structure as the main lane and covered in a simple surface treatment, at least 0.50 m wide. Furthermore, LVR traffic must be monitored and defects that, as soon as they are identified, must be remedied, preventing their severity from increasing and the consequent discomfort and insecurity for users. With the results of this work, it is expected to have contributed to expanding the knowledge about LVR to assist in the expansion of the paved network and the management of this road infrastructure.